Registers of sex offenders - general considerations and data analysis from the register in Serbia - Srnić-Nerac Jelena; Kovačev Milica (Temida)
In addition to criminalizing both traditional and new offences against sexual freedom, most countries, including Serbia, have introduced specific measures for addressing sexual offenses. These measures include the mandatory collection and recording of offenders‘ personal data in special registers. In Serbia, more than 10 years ago, a special register was established for those convicted of crimes against sexual freedom involving minors. This paper presents a basic analysis of the data recorded in the register since its inception. The analysis results indicate that the most prevalent offence is unauthorized sexual acts, and imprisonment is the most commonly imposed criminal sanction. Detected cases of recidivism so far indicate a low rate of reoffending. On the other hand, nearly one-third of the imposed sanctions are house arrest, which involves serving the sentence in the convict‘s residence, raising debates about the purpose of punishment, victim protection, and the application of other special measures. The authors conclude that it is necessary to consider whether the register contributes to victim protection and devise ways to use the knowledge gained from analyzing register data in the development of new legislative solutions.